The Transition from Small to Large Farms in Developing Economies: A Welfare Analysis. Issue 1 (1st March 2021) - Ma, Meilin; Lin, Jessie; Sexton, Richard J.
Abstract : Promoting smallholder production systems as a growth and poverty‐reduction strategy versus supporting an institutional framework that enables endogenous and voluntary consolidation of smallholder farms into larger operations is a central debate for economic development and food security in low‐ and middle‐income countries. We propose an integrated conceptual framework to compare the two alternative farming systems for producing a domestic staple commodity, focusing on key economic factors that differentiate them, including labor inefficiency of larger farms, credit constraints for smallholders, and differences in farm–retail price spreads. We derive equilibrium expressions for economic welfare for smallholder farmers and urban consumers under the two farming systems, and parameterize the model based on publicly available data and recent empirical literature. An extensive simulation analysis reveals several key results from transforming to a large‐farm equilibrium: ( a ) rural household welfare almost always declines; ( b ) total production of the staple almost always increases; ( c ) the sum of urban and rural household welfare almost always increases, often by substantial amounts; and ( d ) rural employment does not decrease, even with modest increases in capital intensity on large farms. Policies to promote farm consolidation, while protecting rural households from welfare losses, for example through income transfers, can achieve Pareto improvements for nearly all of the comparative equilibria studied.